Facilitating adoption of electric buses through policy: Learnings from a trial in Norway. (August 2021) - Thorne, Rebecca Jayne; Hovi, Inger Beate; Figenbaum, Erik; Pinchasik, Daniel Ruben; Amundsen, Astrid Helene; Hagman, Rolf
Abstract: Learning from first experiences of battery-electric bus (E-bus) trials is important to facilitate uptake and develop effective public policy. Here we present initial E-bus trials in Oslo and use the case to 1) model total cost of ownership (TCO) of E-buses vs. diesel buses, and 2) discuss challenges, opportunities, and policy implications. Together, this yields a holistic analysis of requirements for speeding up E-bus adoption, spanning operators and policymakers. Results revealed that rapid E-bus roll-out was achieved through successful contract change order use combined with authority support to reduce operator risk. Challenges were encountered surrounding technical issues, climatization energy use and infrastructure establishment in dense urban areas. In addition, urban E-bus TCO is currently high, and since operation is mostly tender controlled with investment costs covered, higher costs must be covered by public budgets. Despite challenges, operators are positive to further E-bus use, suggesting that companies are willing to support innovation when financial risk is low. We expect E-bus operation to become competitive to diesel buses in Oslo by 2025; to facilitate adoption before economic parity, municipalities and transport authorities must continue to play a large role. Further regulation is also urgently needed to facilitate common infrastructure planning and development. Highlights: Rapid E-bus uptake was realized by contract change-orders and authority support. Key trial challenges were establishing infrastructure, auxiliary energy supply and costs. Companies are willing to support innovation when financial risk is low. Authorities must play a large role until cost parity with diesel buses is reached. Regulation for planning and facilitating fast-charging infrastructure is needed.